PENILAIAN RASIONALITAS PENGGUNAAN ANTIBIOTIK PADA PASIEN USIA 1-5 TAHUN DENGAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) DI PUSKESMAS CIMAHI TENGAH - Sri Wahyuningsih; Faizal Hermanto; Andreanus A Soemardji; Riza Amelia; Yuliana Agustin (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Acute Respiratory Infection (ARI) is a disease that commonly occurs in children aged 1–5 years. Irrational use of antibiotics can cause bacterial resistance and unwanted side effects. This study aims to assess the rationality of antibiotic use in ISPA patients aged 1–5 years at the Central Cimahi Health Center in January–December 2022. The Central Cimahi Health Center conducted this descriptive study. This involves collecting retrospective prescription data from individuals aged 1–5 years throughout the period from January 2022 to December 2022. Data collection uses a saturated sampling method, where the total population is 526 prescriptions and prescriptions that do not meet the inclusion criteria and duplicates are 469 prescriptions, resulting in a total sample size of This research analyzed 56 recipes, both quantitatively and qualitatively. The evaluation of rationality includes the criteria for the right indication, the right drug, the right patient, and the right dose. The results show that the highest ARI characteristics are at the age of one year, namely 27% and the highest gender occurs in boys at 55%. The rationality of antibiotic use based on the criteria of right indication, right drug, right patient, and right dose shows a percentage of 100%. The Central Cimahi Community Health Center evaluates the rationality of antibiotic use in ISPA patients aged 1-5 years as rational